FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, AND FINANCIAL MANAGEMENT BEHAVIOR: SELF–CONTROL AS MEDIATING - Siswanti, Indra (Accounting Department,, 2020)
ABSTRACTPurpose — This research aims to analyze the factors influencing financial management behavior in employees of Islamic University